Intraperitoneal insulin infusion: on the way to the artificial pancreas - Vladimir Aleksandrovich Karpel'ev (Endocrinology Research Centre, 2015)
Creating an "artificial pancreas" (a "closed loop" insulin pump, with self-adjusting insulin abilities, based on real time continuous glucose monitoring data) – is one of the most actual medical challenges of modern engineering and cybernetics.Artificial pancreas (AP) prototypes based on wearable insulin pump with subcutaneous insulin delivery are still problematic, mainly because of slow insulin pharmacokinetics. Intravenous insulin infusion via AP allows effectively maintain euglycaemia for inpatients, due to insulin pharmacokinetics and pharmacodynamics advantages. Unfortunately, it can’t be used for outpatients. Intraperitoneal insulin infusion is still relatively infrequently used in the world, but it is a promising alternative, compared to both previous methods due to a physiological action profile, fast insulin pharmacokinetics, relatively better safety and availability for outpatient usage.The purpose of this review is to describe the intraperitoneal insulin infusion features for diabetes patients at a point of AP creation perspectives.